2010
DOI: 10.4238/vol9-3gmr882
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of epidemiological studies of association of P53 codon 72 polymorphism with bladder cancer

Abstract: ABSTRACT. Although there have been many studies investigating a possible association between p53 codon 72 polymorphism and risk of bladder cancer, the results have been inconsistent. We conducted a meta-analysis of six epidemiological studies, which included 597 bladder cancer cases and 731 controls. Patients with bladder cancer had a significantly lower frequency of Pro/Arg [odds ratio (OR) = 0.80, 95% confidence interval (CI) = 0.64-0.99], when compared to controls. Stratifying for race, we found that among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…A meta-analysis of 33 case-control studies involving a total of 16,706 subjects, conducted by Jiang et al (23), suggested that glutathione S-transferase M1 mu1 status is associated with a significant increase in the risk of bladder cancer. Additionally, a meta-analysis of 6 case-control studies involving a total of 1,328 subjects, conducted by Li et al (24), reported that a polymorphism in p53 codon 72 is associated with bladder cancer and that the genotypic distribution of this polymorphism may vary with the stage of bladder cancer. Furthermore, a meta-analysis of 10 case-control studies involving a total of 3,549 subjects, conducted by Jiang et al (25), reported that the TP53 Arg72Pro genotype may increase the susceptibility to bladder cancer in Asian individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 33 case-control studies involving a total of 16,706 subjects, conducted by Jiang et al (23), suggested that glutathione S-transferase M1 mu1 status is associated with a significant increase in the risk of bladder cancer. Additionally, a meta-analysis of 6 case-control studies involving a total of 1,328 subjects, conducted by Li et al (24), reported that a polymorphism in p53 codon 72 is associated with bladder cancer and that the genotypic distribution of this polymorphism may vary with the stage of bladder cancer. Furthermore, a meta-analysis of 10 case-control studies involving a total of 3,549 subjects, conducted by Jiang et al (25), reported that the TP53 Arg72Pro genotype may increase the susceptibility to bladder cancer in Asian individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Sergentanis and Economopoulos (Sergentanis and Economopoulos, 2010b) showed an enhancement of the association between the C allele and cancer, both breast cancer and lung cancer, with increasing latitude. Similar ethnicity-specific contribution of TP53 rs1042522 germline variation is also typical for other human cancers (Table 2) Gao et al, 2009;Jiang et al, 2010a;Li et al, 2010;Liu et al, 2011;Zhang et al, 2010a). Interestingly enough, the allelic expression of human genes, like allele frequency, was found to differ between ethnic groups (Spielman et al, 2007).…”
Section: Tp53 Polymorphisms: the Cancer Predisposing Effect And Ethnimentioning
confidence: 60%
“…A high heterogeneity of results was observed in breast Hu et al, 2010b;Lu et al, 2011b;Ma et al, 2011;Peng et al, 2011;Sergentanis and Economopoulos, 2010b;The Breast Cancer Association Consortium, 2006;Zhang et al, 2010b;Zhuo et al, 2009a), colon and rectum (Dahabreh et al, 2010;Liu et al, 2011;Tang et al, 2010;Wang et al, 2010b) cancers. Though still not quite clear, cancer of the ovary (Schildkraut et al, 2009;Zhang et al, 2008), endometrium (Francisco et al, 2010;Jiang et al, 2010b), stomach (Francisco et al, 2010;Gao et al, 2009;Liu et al, 2011), bladder (Jiang et al, 2010a;Li et al, 2010), prostate Zhang et al, 2011b;Zhu et al, 2011), and skin (Francisco et al, 2010;Jiang et al, 2011) appear to be affected. As for the rs17878362 polymorphism, a clear association of the A2 allele with a high risk of breast cancer Hu et al, 2010a;Hu et al, 2010b;Zhang et al, 2011a) and a lack of involvement in lung (Hu et al, 2010a), ovary (Schildkraut et al, 2009), colon and rectum (Hu et al, 2010a) cancer susceptibility has been demonstrated.…”
Section: Tp53 Polymorphisms: the Cancer Predisposing Valuementioning
confidence: 99%
“…The findings of Cao et al (2009) also indicated that p53 Pro72 variant is associated with an increased risk for colorectal cancer in the Korean population. In addition, the p53 codon 72 polymorphism associations with bladder cancer and that genotypic distribution of this polymorphism were showed by Li et al (2010) in China. In agreement with prior studies on breast, colorectal and prostate cancer in Iran, we found significant differences in the genotype or allele frequencies between the patients and the control groups (Mojtahedi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A guanine/cytosine variant at the second position of codon 72 on exon 4 leads to Arg72 or Pro72 protein variants with markedly altered primary structures and different biochemical functions. The current view is that the P53-Arg72 protein is more effective than the P53-Pro72 protein at inducing apoptosis and protecting cells from tumor development (Li et al, 2010;Huang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%